Hardware Module for the Security Enhancement of Optical Telecom Network Equipment - Nadeem, M.; Ali, M. (The Nucleus, 2015)
The telecommunication equipment physical security threats have increased not only in Pakistan but also anywhere in the world and hence, reducing the revenue. This new challenging and alarming situation is created for the telecom network provider. The main focus of this paper is to provide a low cost economical design for reducing the theft of the costly telecommunication equipment like optical network units (ONU). This system is based on instant messaging on the mobile in the event of theft through GSM modem. The proposed security module is dynamic, flexible and can also be integrated in the existing networks and separately having its own independent low power consumption source. The module will continuously work successfully under different scenarios such as completely isolated from other devices by power break down or by fibre cut.